Cross-Cutting Themes in Economies with Large Banking Systems. (Policy Papers; Policy Paper, 2010)
Recent events make clear that the global economy remains vulnerable, and that important work remains to be done to secure the recovery and prevent future crises. We must adapt to new challenges and ensure that the institution is equipped with the right tools to assess pressing risks to global stability and, when crisis prevention efforts are not enough, with the right instruments to restore confidence.